Clinical course of sepsis, severe sepsis, and septic shock in a cohort of infected patients from ten Colombian hospitals (2013)
ABSTARCT: Sepsis has several clinical stages, and mortality rates are different for each stage. Our goal was to establish the evolution and the determinants of the progression of clinical stages, from infection to septic shock, over the first week, as well as their relationship to 7-day and 28-day mortality.